Effect of Co-Cr alloy recasting on the fracture toughness - Resti Efrata Eka; Rini Dharmastiti; Widjijono Widjijono (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Frame denture generally uses Co-Cr alloy. However, alloy is expensive, so dental laboratories use residual sprue casting for recasting. The purpose of this study was to determine the effect of Co-Cr alloy recasting on fracture toughness. This was a laboratory experiment, with five sample groups, namely R0: 100% of new alloys; R1: 50% one-time recasting procedure and 50% new alloys, R2: 50% two-time recasting procedure and 50% new alloys, R3: 50% three-time recasting procedure and 50% new alloys, R4: 50% four-time recasting procedure and 50% new alloys. Fracture toughness was tested using a universal testing machine; the data were analyzed by One-Way Anova test and LSD (p>0.05). The results showed that the fracture toughness was 233.103 MPa-m1/2 in R4, and the highest was 242.435 MPa-m1/2 in R0. The results of the analysis by the LSD test on fracture toughness showed that there were no significant differences in R0 with R1 and R2, but there were significant differences between R0 with R3 and R4. There was a decrease after recasting in each group because of the missing elements of the Co-Cr alloy. The percentage of each element decreased due to oxidation and evaporation during heating. There was a change in the composition of the Co-Cr alloy in R3 and R4. There was a decrease in the fracture toughness. Variation in recasting frequency of Co-Cr alloy affected the fracture toughness. In each sample groups, the fracture toughness of Co-Cr alloy decreased after recasting.